GABA tonic currents and glial cells are altered during epileptogenesis in a mouse model of Dravet syndrome - Goisis, Rosa Chiara; Chiavegato, Angela; Gomez-Gonzalo, Marta; Marcon, Iacopo; Requie, Linda Maria; Scholze, Petra; Carmignoto, Giorgio; Losi, Gabriele (Frontiers in Cellular Neuroscience, 2022)
Dravet Syndrome (DS) is a rare autosomic encephalopathy with epilepsy linked to Nav1.1 channel mutations and defective GABAergic signaling. Effective therapies for this syndrome are lacking, urging a better comprehension of the mechanisms involved. In a recognized mouse model of DS, we studied GABA tonic current, a form of inhibition largely neglected in DS, in brain slices from developing mice before spontaneous seizures are reported. In neurons from temporal cortex (TeCx) and CA1 region GABA tonic current was reduced in DS mice compared to controls, while in entorhinal cortex (ECx) it was not affected. In this region however allopregnanonole potentiation of GABA tonic current was reduced in DS mice, suggesting altered extrasynaptic GABAA subunits. Using THIP as a selective agonist, we found reduced d subunit mediated tonic currents in ECx of DS mice. Unexpectedly in dentate gyrus (DG), a region with high d subunit expression, THIP-evoked currents in DS mice were larger than controls. Immunofluorescence study confirmed that d subunit expression was reduced in ECx and increased in DG of DS mice. Finally, considering the importance of neuroinflammation in epilepsy and neurodevelopmental disorders, we evaluated classical markers of glia activation. Our results show that DS mice have increased Iba1 reactivity and GFAP expression in both ECx and DG, compared to controls. Altogether we report that before spontaneous seizures, DS mice develop significant alterations of GABA tonic currents and glial cell activation. Understanding all the mechanisms involved in these alterations during disease maturation and progression may unveil new therapeutic targets.